Development of Problem-Based Physics Teaching Modules on Climate Change and Weather for High Schools - Irenta Irenta; Hamdi Akhsan; Kistiono Kistiono (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2026)
Climate change and weather are now problems that affect the whole world and are bad for the environment and for people's lives. Sadly, a lot of high school students still don't understand the basics of climate change because the material is too abstract and hard to understand. For example, they think that daily weather is a form of long-term climate change. To solve this, a Problem-Based Learning (PBL) physics module was made for high school students to teach them the basics of climate change and weather. The module was created to follow the Merdeka Curriculum's Deep Learning principles of being mindful, meaningful, and fun. This study employed an R&D methodology utilizing the ADDIE model. Three experts (in material, curriculum, and pedagogy) were involved in the validation process. 23 students were used in individual and small group trials to test practicality. The average validity score was 86.78% and the average practicality score was 82.82%. Both of these scores are in the Very Valid and Very Practical ranges. These results show that the module is a good choice for use as a contextual teaching tool that helps with understanding concepts, engaging the mind, and being aware of the environment.